MacJannet campers seated outside of a tipi (teepee) and dressed in Native American costumes, ca. September 1962 - MacJannet, Donald (Tufts Archival Research Center, 2005)
2x2 color slide; taken from MS024/007-073 - "Donald MacJannet slides from travel and camp"